ANALISIS PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK ORGANISASI TERHADAP PENGEMBANGAN KARIER PEGAWAI PADA PT. ALAM DAMAI MITRA RAYA MAGETAN - Rahayu Triastity, Anang Sujatmiko, Amin Wahyudi & (Universitas Slamet Riyadi, 2018)
Career development within a company is influenced by individual characteristics and organizational characteristics. This study aims to determine the effect of individual characteristics which include individual expertise and organizational characteristics which include organizational resources, organizational climate and organizational structure on employee career development at PT. Alam Damai Mitra Raya Magetan. The population in this study were 278 employees and used a sample of 139 respondents. Data collection methods using questionnaires, interviews and data analysis techniques used are validity and reliability testing; classical assumption test, multiple linear regression analysis; t test, F test and coefficient of determination (RÂ²). The results showed that the regression results of independent variables (individual skills, organizational resources, organizational climate and organizational structure) with career development showed RÂ² of 0,426. This means that 42,6% of variations in career development variables are explained by independent variables and the remaining 57,4% illustrates the existence of other free variations that are not observed in this study such as leadership and organizational support. Keywords: expertise, resources, organizational climate, structure, career development